When the Gromov-Hausdorff Distance Between Finite-Dimensional Space and Its Subset Is Finite? (Communications in Mathematical Research, 2025)
In this paper we prove that the Gromov-Hausdorff distance between $\mathbb{R}^n$ and its subset $A$ is finite if and only if $A$ is an $ε$-net in $\mathbb{R}^n$ for some $ε > 0.$ For infinite-dimensional Euclidean spaces this is not true. The proof is essentially based on upper estimate of the Euclidean Gromov-Hausdorff distance bymeans of the Gromov-Hausdorff distance.